Assessment of insulin action and glucose effectiveness in diabetic and nondiabetic humans. - Alzaid, A A (1994)
Insulin concentrations in humans continuously change and typically increase only when glucose also increases such as with eating. In this setting, it is not known whether the severity of hepatic and extrahepatic insulin resistance is comparable and whether the ability of glucose to regulate its own uptake and release is defective in non-insulin-dependent diabetes mellitus (NIDDM). To address this question, NIDDM and nondiabetic subjects were studied when glucose concentrations were clamped at either 5 mM (euglycemia) or varied so as to mimic the glucose concentrations observed in nondiabetic humans after food ingestion (hyperglycemia). Insulin was infused so as to simulate a "nondiabetic" postprandial profile. During euglycemia, insulin increased glucose disposal in nondiabetic but not diabetic subjects indicating marked extrahepatic resistance. In contrast, insulin-induced suppression of glucose release was only minimally less (P < 0.05) in diabetic than nondiabetic subjects (-1.06 +/- 0.09 vs. -1.47 +/- 0.21 nmol.kg-1 per 4 h). Hyperglycemia substantially enhanced disposal in both groups. Glucose effectiveness measured as the magnitude of enhancement of disposal (0.59 +/- 0.18 vs. 0.62 +/- 0.17 nmollkg-1 per 4 h) and suppression of release (-0.36 +/- 0.12 vs. -0.14 +/- 0.12 nmol.kg-1 per 4 h) did not differ in the diabetic and nondiabetic subjects. In conclusion, when assessed in the presence of a physiological insulin profile, people with NIDDM demonstrate: (a) profound extrahepatic insulin resistance, (b) modest hepatic insulin resistance, and (c) normal ability of glucose to stimulate its own uptake and suppress its own release.